Bibliometric Analysis of Post Covid-19 Management Strategies and Policies in Hospitality and Tourism - Khan, Kanwal Iqbal; Nasir, Adeel; Saleem, Saima (Frontiers in Psychology, 2021)
The strategic perspective of management policies gained utmost importance during the post-Covid era. The researchers are trying to introduce strategies that can help organizations cope with post-crisis destruction. Yet, the research on the topic is fragmented, mainly related to the hospitality and tourism industry. This paper aims to present scholarly research findings dealing with the post-Covid-19 management strategies in the hospitality and tourism industry from January 1, 2020, to July 28, 2021. These strategies can play an essential role in the survival and growth of the sectors. The study identified and acknowledged the core contributing authors, journals, countries, affiliation, corresponding authors through bibliometric, citation and keyword analysis. It also conducted the co-occurrence analysis and reported three significant research streams and bibliometric coupling to identify four research themes for management strategies of the tourism and hospitality industry in the post-COVID era. With the help of an influential and conceptual framework, the study highlights the future challenges managers could face and suggested the possible area for reviewing and revising the existing policies by proposing future directions. Consequently, this study contributes to the current literature on post-Covid-19 management strategies and policies by developing the critical analysis of the extant literature and highlighting the understudy areas that future studies must explore to expand the scope of the research.